Developmental Education in Dutch primary schools: Review of research outcomes from a CHAT-based teaching approach. (February 2022) - Oudes-Slob, Leanne; Dobber, Marjolein; van der Veen, Chiel; van Oers, Bert
Abstract: In this literature review, we evaluate the learning outcomes of Developmental Education (DE) in The Netherlands. This CHAT-based teaching approach has been around for over 30 years and is constantly being developed in collaboration between teachers, teacher educators and researchers. Although outcomes of this approach are evaluated in educational practice and several research studies, no systematic review study has been carried out to present an overview of the learning outcomes of DE. Therefore, we conducted a systematic narrative literature review study. We found that research in the field of DE varies both in domain and design. We conclude that pupils in DE meet national norms on language development, show sufficient to good scores on mathematical development and seem to have higher scores on social-emotional development compared to pupils in non-DE schools. These conclusions should be interpreted with caution, as this review study includes mainly small-scaled studies. Therefore, we recommend that future studies should adopt a longitudinal design, include more schools and pupils, and apply appropriate tests to evaluate the learning outcomes in a way that fits the DE approach.